Abnormal increase of intraocular pressure in fellow eye after severe ocular trauma: A case report. Issue 31 (August 2016) - Vaajanen, Anu; Tuulonen, Anja
Abstract: Background: An ocular injury can lead to secondary glaucoma in the traumatized eye in 3% to 20% of cases. Literature on the risk of developing elevated intraocular pressure in the nontraumatized fellow eye is scant. Clinicians treating ocular traumas should also bear in mind sympathetic ophthalmia, a rare bilateral granulomatous panuveitis following accidental or surgical trauma to 1 eye. Case report: We report a case of high-pressure glaucoma of the fellow eye without any signs of uveitis. The left eye of a 24-year-old man was injured in an inadvertent movement during a free-time table-tennis match. The eye was severely crushed, leading to blindness. His right eye developed medically uncontrolled high-pressure glaucoma only 1 month after the injury. Conclusion: To the best of our knowledge, there are no previous reports of post-traumatic glaucoma in the nontraumatized eye after open-globe injury.